Repurposing everyday technologies to provide just-in-time visual supports to children with intellectual disability and autism: a pilot feasibility study with the Apple Watch®. (2nd October 2017) - Schlosser, Ralf W.; O'Brien, Amanda; Yu, Christina; Abramson, Jennifer; Allen, Anna A.; Flynn, Suzanne; Shane, Howard C.
Abstract : Objectives: Everyday technologies (e.g. iPads, smart phones, Apple Watch®) might be successfully repurposed to meet the needs of children with disabilities. Although visual supports are an empirically supported treatment, they are typically not provided just-in-time (JIT). In this study, we aimed to provide JIT visual supports in the form of scene cues (representative photos or video clips) to augment spoken input to children with a dual diagnosis of intellectual disability and autism. The objectives of this study were to (a) explore whether JIT-delivered scene cues permit these children to implement directives they were unable to complete with speech alone, and (b) test the feasibility of providing scene cues on the Apple Watch® with a focus on display size. Methods: Using a case series design, five children with an intellectual disability and autism were presented with directives and required to carry out the directives with figurines and objects as a table top activity. Initially, each directive was presented in spoken form only, and static scene cues (photos) and subsequently dynamic scene cues (video clips) were provided as augmented input as needed (JIT). Results: The hierarchical JIT visual supports enabled the five children with intellectual disability and autism to carry out the majority of directives. Conclusions: The relatively small display size of the Apple Watch does not seem to hinder children with a dual diagnosis of intellectual disability and autism to glean critical information from visual supports. The JIT provision of scene cues resulted in successful directive-following in these children.